Molecular Mechanisms of Phthalate-Induced Hepatic Injury and Amelioration by Plant-Based Principles - Lalit Kumar Singh; Rashmi Pandey; Nikhat Jamal Siddiqi; Bechan Sharma (Toxics)
Phthalates are the emerging environmental toxicants derived from phthalic acid and its constituents, which are moderately present in plastics and many personal care products. Phthalate exposure occurs through various environmental factors, including air, water, and soil, with absorption facilitated via ingestion, inhalation, and dermal contact. Upon exposure, phthalates become bioavailable within the biological systems and undergo biotransformation and detoxification processes in the liver. The physicochemical properties of phthalates indicate their lipophilicity, environmental persistence, and bioaccumulation potential, influencing their absorption, distribution, and hepatic biotransformation. The prolonged exposure to phthalates adversely influences the biological redox system by altering the levels of the enzymatic and non-enzymatic antioxidants, molecular signaling pathways, and causing hepatic pathogenesis. The strategies to combat phthalate-induced toxicity include avoiding exposure to these compounds and using plant-based bioactive molecules such as polyphenols, which possess therapeutic potential as antioxidants, suppress inflammatory cascades, prevent oxidative damage, and stabilize cellular integrity. This review presents a comprehensive and updated account of the chemical, biochemical, immunological, and toxicological properties of phthalates, along with novel plant-based therapeutic strategies to mitigate the phthalate-induced adverse effects on living systems.